ANALYSIS OF THE FINANCIAL CONDITION OF ENTERPRISES IN THE ENERGY SYSTEM - Matnazar Yusupovich Rakhimov (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2025)
The article, based on financial reporting data, evaluates periodic chanGES in important performance indicators of the organization "UzTransgaz", which is an important link in the energy system enterprises.